2010
DOI: 10.1186/cc9157
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of sarcolemmal dystrophin and β-dystroglycan may be a potential mechanism for myocardial dysfunction in severe sepsis

Abstract: Introduction In 2002, the Surviving Sepsis Campaign defi ned a strategy that aimed to reduce the high mortality due to sepsis. One point of this strategy was a recommendation to recognize that sepsis is a frequent cause of death and high economic costs in the pediatric intensive care unit. Knowledge of the disease is the fi rst step to impact it. There are few studies on pediatric sepsis epidemiology in the world and none in Colombia. Hypothesis The epidemiological features of Colombian children are diff erent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This is consistent with our previous data demonstrating that the absence of dystrophin increased susceptibility to viral infection (5). Apart from the loss of dystrophin at the sarcolemma, which has been shown to increase susceptibility to viral infection, there are other genetic and secondary alterations in the dystrophin-glycoprotein complex (DGC) that affect sarcolemmal stability and could affect susceptibility to viral infection (12)(13)(14)(15)(16)(17). Therefore, it is possible that genetic variability in the core components of the DGC or alterations that affect the level of dystrophin expression (such as occurs in Becker muscular dystrophy or X-linked dilated cardiomyopathy) (18) could have a profound permissive or inhibitory effect on susceptibility to enteroviral infection.…”
Section: Figuresupporting
confidence: 81%
“…This is consistent with our previous data demonstrating that the absence of dystrophin increased susceptibility to viral infection (5). Apart from the loss of dystrophin at the sarcolemma, which has been shown to increase susceptibility to viral infection, there are other genetic and secondary alterations in the dystrophin-glycoprotein complex (DGC) that affect sarcolemmal stability and could affect susceptibility to viral infection (12)(13)(14)(15)(16)(17). Therefore, it is possible that genetic variability in the core components of the DGC or alterations that affect the level of dystrophin expression (such as occurs in Becker muscular dystrophy or X-linked dilated cardiomyopathy) (18) could have a profound permissive or inhibitory effect on susceptibility to enteroviral infection.…”
Section: Figuresupporting
confidence: 81%
“…The reduction of connexin-43 and N-cadherin resulted in the loss of structural integrity of intercalated discs, hindering communication between myocardial cells [11]. Subsequently, cardiomyocyte degeneration and lysis of actin and myosin filaments, all caused by sepsis, were associated with reduced expression of dystrophin [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these data Parker thought that LV dilatation were an adaptive mechanism apt to increase systolic stroke through a better utilization of Starling mechanism (early preload adaptation). Successive studies by echocardiography have not confirmed however a significant LV dilatation while observing an altered biventricular relaxation and a systolic dysfunction of the right ventricle in 41% of the p, isolated or in conjunction with a LV dysfunction [182][183][184][185].The apparently better cardiac function in non survivors is currently perceived as a consequence of the persistent septic hemodynamic pattern with decreased SVR causing higher CI and LVEF, both being heavily load-dependent indexes [186]. A LV depressed contractile performance is constant in human and experimental sepsis [187] if related to pre and after-load, it is explained by the global ventricular hypokinesia observed in 60% of the p. in septic shock [188]: the impairment of LV contractility may be unravelled also by the reduction of CI in response to norepinephrine infusion [181].…”
Section: Hemodynamic Patternmentioning
confidence: 99%